2014
DOI: 10.1186/1472-6882-14-288
|View full text |Cite
|
Sign up to set email alerts
|

Flavones from Erythrina falcata are modulators of fear memory

Abstract: BackgroundFlavonoids, which have been identified in a variety of plants, have been demonstrated to elicit beneficial effects on memory. Some studies have reported that flavonoids derived from Erythrina plants can provide such beneficial effects on memory. The aim of this study was to identify the flavonoids present in the stem bark crude extract of Erythrina falcata (CE) and to perform a bioactivity-guided study on conditioned fear memory.MethodsThe secondary metabolites of CE were identified by high performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 68 publications
7
28
0
2
Order By: Relevance
“…Similar results were seen after a single dose treatment with crude extract of Erythrina falcata (CE), pure flavonoids or flavonoid-rich fractions from the stem bark of E. falcata using a one-trial, step-down inhibitory avoidance (IA) [9] or conditioned lick suppression (CLS) [8] tasks.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar results were seen after a single dose treatment with crude extract of Erythrina falcata (CE), pure flavonoids or flavonoid-rich fractions from the stem bark of E. falcata using a one-trial, step-down inhibitory avoidance (IA) [9] or conditioned lick suppression (CLS) [8] tasks.…”
Section: Introductionsupporting
confidence: 61%
“…Our data has established that the treatment with flavonoidrich plants or flavonoidic molecules resulted in a significant retention of long-term fear memory and its spontaneous recovery evaluated during extinction test sessions, although FfB did not prevent the acquisition of the extinction of fear conditioning within-sessions [6,9]. Moreover, our data showed, through pharmacological manipulation and genetic analysis, that acquisition of lick suppression is mediated by hydroxytryptamine (serotonin) receptor, subunit 1A (5-HT 1A R), gamma-aminobutyric acid type A receptor (GABA A R) and GluN2B-NMDAR in the dorsal hippocampal formation (dHF).…”
Section: Flavonoidic Fraction Improves the Acquisition Of Fear Memorymentioning
confidence: 99%
“…For various reasons, these preceding researches have been focused toward the medium polar constituents of the E. abyssinica stem bark, while the knowledge concerning to the most polar secondary metabolites remains limited up to now. In contrast, the stem bark from other Erythrina species have been previously studied for their polar constituents, resulting in the isolation of other classes of secondary metabolites such as triterpenoid saponins (Kouam et al, 1991(Kouam et al, , 2007(Kouam et al, , 2008Mbafor et al, 1997), also found to exert a wide range of pharmacological properties including cytotoxicity (Podolak et al, 2010), and most recently C-glycosyl flavones (De Oliveira et al, 2014). Though flavonoids most often are distinguished by their antioxidant, antiallergic and anti-inflammatory activities, some representative cases such as quercetin, catechin, gallocatechin and apigenin have been investigated as potential chemopreventive or chemotherapeutic agents against cancer (Di Carlo et al, 1999;Marchand, 2002).…”
Section: Introductionmentioning
confidence: 93%
“…T anticonvulsant, myorelaxant and cognitive-impairing effects (de Oliveira et al, 2014(de Oliveira et al, , 2015Griffin et al, 2013;Rich et al, 2006;Verwey et al, 2005).…”
Section: Introductionmentioning
confidence: 99%